2017
DOI: 10.1186/s40729-017-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and degradation properties of advanced platelet-rich fibrin (A-PRF), concentrated growth factors (CGF), and platelet-poor plasma-derived fibrin (PPTF)

Abstract: BackgroundFibrin clot membranes prepared from advanced platelet-rich fibrin (A-PRF) or concentrated growth factors (CGF), despite their relatively rapid biodegradability, have been used as bioactive barrier membranes for alveolar bone tissue regeneration. As the membranes degrade, it is thought that the growth factors are gradually released. However, the mechanical and degradable properties of these membranes have not well been characterized. The purpose of this study was to mechanically and chemically charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 16 publications
6
85
0
3
Order By: Relevance
“…15 In accordance with the strategy of periodontal intrabony defect regeneration, platelet concentrates could be used for the RST of periimplantitis as a barrier membrane, and be combined with grafts to enhance bone healing. 18 While CGF has been stated to be an improved formulation of PRF, 19 it has also been proposed that a different term is used for CGF because of the use of a different centrifuge machine (MEDIFUGE, Silfradent srl, S. Sofia, Italy) and centrifugation speed (2400 to 3000 rpm). 16,17 Concentrated growth factors (CGF) were introduced by Sacco as a therapeutic protocol obtained by separation from centrifuged venous blood using a special device in the same manner as PRF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 In accordance with the strategy of periodontal intrabony defect regeneration, platelet concentrates could be used for the RST of periimplantitis as a barrier membrane, and be combined with grafts to enhance bone healing. 18 While CGF has been stated to be an improved formulation of PRF, 19 it has also been proposed that a different term is used for CGF because of the use of a different centrifuge machine (MEDIFUGE, Silfradent srl, S. Sofia, Italy) and centrifugation speed (2400 to 3000 rpm). 16,17 Concentrated growth factors (CGF) were introduced by Sacco as a therapeutic protocol obtained by separation from centrifuged venous blood using a special device in the same manner as PRF.…”
mentioning
confidence: 99%
“…16,17 Concentrated growth factors (CGF) were introduced by Sacco as a therapeutic protocol obtained by separation from centrifuged venous blood using a special device in the same manner as PRF. 18 While CGF has been stated to be an improved formulation of PRF, 19 it has also been proposed that a different term is used for CGF because of the use of a different centrifuge machine (MEDIFUGE, Silfradent srl, S. Sofia, Italy) and centrifugation speed (2400 to 3000 rpm). 20 Furthermore, CGF has been found to be almost identical to self-clotted advanced-PRF (A-PRF) in respect of mechanical and degradation properties.…”
mentioning
confidence: 99%
“…In general, it is thought that the ability of growth factor retention depends on the mechanism of growth factor adhesion and/or storage, while the release ability depends mainly on the degradability of cross‐linked fibrin fibers. However, assuming that the degradability is almost equal between A‐PRF and CGF matrices, as was demonstrated in our previous study, their release ability can be considered largely influenced by the retention ability. Thus, it is the manner of growth factor distribution.…”
Section: Introductionmentioning
confidence: 64%
“…[16][17][18][19][20] We have compared the mechanical and degradation properties of advanced PRF (A-PRF) and concentrated growth factors (CGF) and found no statistically significant differences. 18 The current main topic in the comparison of PRF is their abilities to retain and release growth factors. 16,19,21 In some studies, 19,21 an A-PRF matrix prepared by low-speed centrifugation has been demonstrated to be superior to a CGF matrix prepared by high-speed centrifugation.…”
Section: Many Research Investigations Have Recently Been Performedmentioning
confidence: 99%
See 1 more Smart Citation